2021
DOI: 10.3389/fmed.2021.692060
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic Features Summarization and Comparison of Four Types of Cutaneous Vascular Anomalies

Abstract: Objective: Dermoscopic features of cutaneous vascular anomalies have been reported, but the described features currently known are limited and not well-understood. The aim of this study is to comprehensively summarize and compare the dermoscopic features of the four different types of cutaneous vascular anomalies [infantile hemangiomas (IH), cherry angioma (CA), angiokeratomas (AK), and pyogenic granuloma (PG)] in the Chinese Han population.Materials and Methods: Dermoscopic features of 31 IH, 172 CA, 31 AK, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
9
1
Order By: Relevance
“…Such findings are not observed in other haemangiomas. 5 These liner irregular vessels may reflect dilated capillaries that have no choice but to run in the shallow dermis due to compression by the enlarged glomerular haemangioma in the dermis. The diagnosis of POEMS syndrome is often difficult.…”
mentioning
confidence: 99%
“…Such findings are not observed in other haemangiomas. 5 These liner irregular vessels may reflect dilated capillaries that have no choice but to run in the shallow dermis due to compression by the enlarged glomerular haemangioma in the dermis. The diagnosis of POEMS syndrome is often difficult.…”
mentioning
confidence: 99%
“…Vascular structures beyond lacunae include linear curved vessels, serpiginous vessels, and coiled vessels (Figure 9). Lesions with multiple structures may display reticular, unspecific, or clustered vessel distribution [41,42]. It was previously shown that after HIFU treatment, a mild urticarial response occurred but resolved within hours [43].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of adult hemangioma, we could observe the circular endothelial wall of these capillaries throughout the epidermis and papillary dermis. For clinicians, it is important to differentiate hemangioma from angiokeratoma, which is an acquired benign vascular malformation and a cutaneous sign of Fabry's disease, an X-linked genodermatoses with severe systemic organ involvement and diverse clinical symptoms [46]. Basal cell cancer (BCC) is the most common malignancy among white individuals.…”
Section: Discussionmentioning
confidence: 99%